Study of University Students' Quality of Life and Their Attitude to Health During the Third Pandemic Wave: A Quantitative Research - Evgeni L. NIKOLAEV; Anna N. ZAKHAROVA; Elena Yu. LAZAREVA; Denis V. HARTFELDER; Tamara V. TALANOVA; Galina S. DULINA (Communications of International Proceedings, 2022)
An in-depth scientific study of health, quality of life, and well-being of an individual has become especially relevant and scientifically significant in the social reality of the COVID-19 pandemic,. The article highlights the results of an empirical study in the context of the third wave of the COVID-19 pandemic of the quality of life and the profile of a healthy lifestyle of students on such components as "responsibility for health", "physical activity", "nutrition", "internal growth", "interpersonal relationships”, “stress management; the psychological components of attitudes towards health were also studied. The results obtained indicate that attitudes towards health can determine attitudes towards vaccination and the choice of behavioral strategies in a pandemic. Significant differences in attitudes towards health among young men and women were revealed, including in terms of “factors affecting health” and “reasons for insufficient care for health”. At the same time, health values are more significant for young women than for young men; to maintain health, male students try to maintain good physical shape, and women use interpersonal interactions more, which will help them get help and support from relatives and friends. The results of the study became the basis for a psycho-prophylactic program to improve the quality of life and the formation of healthy behavior of Russian university students in a pandemic.
Keywords: third wave of the pandemic; university students; healthy lifestyle profile; quality of life; attitude to health.